Characteristics of patients with rapid eye movement-related obstructive sleep apnea: a retrospective review of 52 patients at a tertiary care center - Hawari, Muhannad; Jamil, Mohamad Gayath; Hemideh, Sanaa; Alharbi, Ayman (International Journal of Advances in Medicine, 2020)
Background: The term “rapid eye movement (REM)-related obstructive sleep apnea (OSA)” is commonly used to describe sleep disordered breathing that occurs exclusively in REM sleep. The prevalence of REM-related OSA ranges from 10% to 36%. Despite the presence of reports describing the features of REM-related OSA, there is still much more to be known about it. Methods: In this study we did retrospective review of 734 patients who had a diagnostic sleep study in a sleep lab at a tertiary center between January 2014 and August 2016 were reviewed. Results: We found that hypertension was found in the charts of 50 patients, 36 of them were diagnosed with hypertension and on medical therapy (72%), 11 patients (out of 50) had diabetes (22%) and 9 (out of 49) had dyslipidemia. 2 patients (out of 49) had Ischemic heart disease (4%), 1 patient (out of 49) had stroke (2%) and 3 patients (out of 49) had arrhythmias (6%). 8 patients (out of 49) had thyroid disease (16%). Conclusions: In conclusion Most patients had mild REM related OSA and most did not have subjective EDS. Hypertension was the most common comorbidity among our patients.